POLITIK IDENTITAS DAN KRISIS IDENTITAS: MENGUNGKAP REALITAS PRAKTEK POLITIK DI INDONESIA - Toguan Rambe; Seva Mayasari (IAIN Padangsidimpuan, 2022)
This paper is the result of research with the argument that the Indonesian nation as a nation state does not justify the polarization of political identity based on ethnicity or religion. The fact that identity politics often occurs is based on certain political interests and for the interests of a group or group in gaining legitimacy of power. This condition causes prolonged social conflict and does not contribute to the development of social solidarity and the development of a nation. While this type of research is descriptive-analytic in the form of narratives presented with accurate data, data collection through library research, the author provides a comprehensive analysis of various written literature and those sourced from print and electronic media. The direction of this paper seeks to portray the nuances of identity politics that occur in Indonesia, how identity politics is played by political actors and what are the implications for the identity of the Indonesian nation. The results of this study indicate that identity politics has a negative impact on Pancasila values and social norms that have become the characteristics of the Indonesian nation. Identity politics also has implications for the identity crisis, among others, disrupting the integrity of the unitary state of the Republic of Indonesia, the increasing prevalence of hoax news, the occurrence of propaganda politics for unilateral interests, disturbing the plurality of the nation and the occurrence of social conflicts.